Modified-Ricatti approach to partially solvable quantum Hamiltonians. II: Morse oscillator related family - Montemayor, Rafael; Salem, L. D. (Comisión Nacional de Energía Atómica; Argentina)
Fil: Montemayor, Rafael Comisión Nacional de Energía Atómica; Argentina